PENGARUH SUBSTITUSI UBI JALAR UNGU TERHADAP KUALITAS CHIFFON CAKE - FITRIADI, FITRIADI; Ruaida, Ruaida; Holinesti, Rahmi (Faculty of Tourism and Hospitality - Universitas Negeri Padang, 2014)
The use of purple sweet potato in food processing is an attempt to diversify the food, one of them is in the processing of chiffon cake. One of the hallmarks of purple sweet potato is high in carbohydrates, have the nutrients needed by the body, has a distinctive color. With use purple sweet potato in chiffon cake in the preparation can improve the external quality (volume, color, and shape) and internal quality (texture,aroma, and flavor) and hedonic on chiffon cake. This study aimed to analyze the effect of different composition of purple sweet potato as much as 10%, 20%, and 30%, of the external quality, internal and hedonic chiffon cake. The type of research is experimental using a completely randomized design with three replications, with 30 panelists. The results of the hypothesis test shows that there is an influence on the level of the commission of the third. Expands the volume level in test of quality, high volume, symmetrical spherical shape, texture soft, delicate porous texture better that the substitution of 10%. Test quality levels better color substitution is at 20%. Level of test quality purple sweet potato aroma, sweetness, flavor purple sweet potato is better at 30%substitution. The quality of the hedonic test is better at 10% substitution . Keywords : Quality Chiffon Cake, Sweet Potato purple.